PENGEMBANGAN KAWASAN SEKITAR STASIUN YANG BERBASIS JALUR KERETA API (RAIL ORIENTED DEVELOPMENT) Studi kasus: Stasiun Pasar Nguter, Sukoharjo, Jawa Tengah - , Christian Nindyaputra Octarino ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Solo-Wonogiri railway is one of the oldest tracks on Java. This pathway plays an important role to connect the city of Solo as a major city with surrounding towns, especially Sukoharjo and Wonogiri. But in fact, this pathway is not functioning optimally. The lack of trains operating on the track and also the lack of passengers makes this track more and more useless. The government has initiated a revitalization program of Solo-Wonogiri railway with the improvement of transport infrastructure and train renewal. Pasar Nguter Station as one of the station passed by Solo-Wonogiri track need to be developed not only the station facilities, but also urban elements in surrounding areas. Rail Oriented Development will be applied to create a compact region where the station as a transit point at its center, and make strong intermodal network in the station area. This study was conducted to determine how far the Station area could be developed based on principles of Rail Oriented Development. The research method is to do a comparison between the existing condition and ideal conditions according to standard theory . The elements are compared according to the study variables, which is related to the mobility, density, diversity, linkage, intermodal in the region. The data obtained through observation is the form of numbers and also a regional mapping based object focus. The research results showed that the Pasar Nguter Station area is still quite far from the ideal conditions of a region-based on Rail Oriented Development. No trains operating on the track make the choice of public transportation become slightly. Elements studied based on the research variable, most still have not reached the ideal condition. Thus itâs needed the right development strategies for creating station area with a strong integration between land use and transportation systems